2021
DOI: 10.3389/fpsyt.2021.691896
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Loneliness, and Boredom Among the General Population of Tyrol, Austria During the COVID-19 Pandemic

Abstract: Background: COVID-19-related mental health problems are considered a public health challenge. The aim of this study was to investigate psychological distress, loneliness, and boredom among the general population of the federal state of Tyrol, Austria.Methods: Residents of Tyrol aged ≥ 18 years were recruited via dissemination of a link through social media and other advertisements and invited to complete an online survey from June 26th to August 20th, 2020. Next to the collection of sociodemographic and COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
(75 reference statements)
2
29
1
Order By: Relevance
“…Women, younger individuals, and people with pre-existing mental health conditions presented with particularly high levels of psychological distress, which corroborates the results of previous studies from different countries 6 , 7 , 9 , 22 27 . In line with the findings of a recent study from the United States 28 , 13.9% of control subjects (67/481) reported psychological distress at baseline relative to 13.1% at follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Women, younger individuals, and people with pre-existing mental health conditions presented with particularly high levels of psychological distress, which corroborates the results of previous studies from different countries 6 , 7 , 9 , 22 27 . In line with the findings of a recent study from the United States 28 , 13.9% of control subjects (67/481) reported psychological distress at baseline relative to 13.1% at follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…All over the world, the prevalence of psychological distress (8)(9)(10) and loneliness (11,12) has increased in the context of the pandemic. Moreover, boredom is a major issue during lockdown that particularly affects women, singles, unemployed, and low-income people (13). In this context, it is important to foster protective factors that can contribute to maintaining psychological stability.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the baseline survey are presented in Tutzer et al ( 14 ) and Chernova et al ( 15 ). Of the 961 baseline participants, 384 took part in the follow-up survey.…”
Section: Resultsmentioning
confidence: 99%
“…Women, single people, and low-income or unemployed people were particularly burdened by these outcomes. Moreover, study participants aged 19–49 reported to be particularly affected by loneliness and boredom ( 14 ). Importantly, the relationship between both study participants' sex and partnership situation and psychological distress and severe loneliness was mediated by resilience, and the relationship between participants' partnership situation and psychological distress was mediated by extraversion ( 15 ).…”
Section: Introductionmentioning
confidence: 99%